APPLICATION OF INDUSTRY 4.0 TECHNOLOGY IN THE IMPROVEMENT OF PLASTIC INJECTION PROCESSES IN A COMPANY IN THE INDUSTRIAL HUB OF MANAUS - Ferreira, Marcos Sidney Castro; Campos, Paola Souto; Leite , Jandecy Cabral (Seven Editora, 2025)
Lead Time optimization ensures compliance with deadlines established with customers, which, in turn, promotes customer satisfaction and loyalty. In addition, the reduction of this time provides a more efficient management of resources, with direct impacts on the reduction of operating costs. This study aimed to implement Industry 4.0 technologies to improve plastic injection processes in a company in the Manaus Industrial Pole (PIM), reducing manufacturing costs, accelerating the Lead Time of device construction and optimizing time in the development of new products. In the methodology, data were collected on the new production processes and the evaluation of the impact of the technology on the reduction of manufacturing costs and the improvement of lead time was carried out, through mapping of the current flow of the process, analysis of production loss reports and production performance data. The results show a significant reduction in lead time, that is, in the time needed to create these devices, which had a period reduced from 35 (thirty-five) to 9 (nine days). 3D printing has also made it possible to create more complex and precise devices, with less material waste, directly contributing to cost reduction and an increase in product quality. DOI:https://doi.org/10.56238/sevened2024.037-153